Improving Peripheral Circulation Through Mindful Movement–Based Diabetic Foot Exercise in Patients with Diabetes Mellitus - Arif Hidayatullah; Solehudin Solehudin (Journal of Innovative and Creativity, 2025)
Diabetes mellitus is a chronic metabolic disorder that often causes peripheral circulatory impairment, increasing the risk of diabetic foot ulcers. Diabetic foot exercise can enhance peripheral perfusion, yet its effectiveness is limited by patients’ lack of movement awareness. The mindful movement approach exercising with full awareness of breathing and bodily sensations is believed to optimize its benefits. The study purpose was evaluate the effect of mindful movement-based diabetic foot exercise on peripheral circulation in patients with type 2 diabetes mellitus. Materials and methods. A quasi-experimental one-group pre-test and post-test design was conducted on 33 respondents at Hidayatullah Medika Clinic, Depok. The intervention was performed once weekly for four weeks, 30 minutes per session. Results. Peripheral circulation was assessed using the Ankle Brachial Index (ABI) before and after the intervention. Paired t-test results showed a significant increase in ABI from 1.03 ± 0.12 to 1.16 ± 0.11 (p = 0.017). Conclusions. Mindful movement-based diabetic foot exercise effectively improves peripheral circulation and can be applied as a simple, non-pharmacological intervention to prevent vascular complications in diabetic patients.